18The Enactment-Externalization Dialectic: Rationalization and the Persistence of Counterproductive Technology Design Practices in Student Engineering - Leonardi, Paul M.; Jackson, Michele H.; Diwan, Amer (Academy of Management Journal, 2009)
This article explores why engineering students are committed to counterproductive practices. Student informants' work practices appeared to coincide with lay stereotypes about what “good engineers” do, and they sought to justify those practices as rational. This externalization encouraged them to perform these practices more frequently. We characterize the relationship between the enactment of norms and the externalization of work practices as a dialectical process that helps explain why the students could not conceive of changing their practices. We draw implications for theory on occupational socialization and for the management of engineering work from our findings.